Use of HLA desensitization in the management of renal transplant recipients in Europe - Rostaing, Lionel P. E.; Böhmig, Georg A.; Taqi, Muhammed Mahdi; Gibbons, Ben (Frontiers in Immunology, 2025)
A significant challenge in kidney transplantation is overcoming immunological barriers such as human leukocyte antigen (HLA) incompatibilities. The presence of anti-HLA antibodies in the transplant candidate is referred to as HLA sensitization. As the degree of sensitization increases, the likelihood of finding a compatible organ decreases. Desensitization is the process of reducing recipient anti-HLA antibodies to acceptable levels to allow transplantation. Enthusiasm for the process has declined with focus turning to optimizing deceased donor allocation and paired kidney exchange programs. This research was designed to assess current practices around desensitization in Europe. A 15-minute online survey with 56 multiple choice or open-ended questions was completed by EU transplant nephrologists, transplant surgeons and nephrologists. Survey topics included kidney transplant caseloads, pre-transplant desensitization and desensitization post-transplant. The results indicate high variation in what physicians consider to be the threshold mean fluorescence intensity (MFI) level for significant anti-HLA antibodies and the need for desensitization. Desensitization protocols are not standardized; while there is alignment on the usage of apheresis and IVIG, usage of other agents is variable. New therapies for desensitization are emerging which could aid in removing immunological barriers to transplantation for the most highly-sensitized patients.